Penentuan Kesetimbangan Adsorpsi Regenerated Spent Bleaching Earth (RSBE) Terhadap Ion Fe(III) - Mhd Taufik Kurniawan; Yusnimar Yusnimar; Sri Helianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Spent Bleaching Earth (SBE) is a waste of palm oil refinery industry. One of the efforts to control the SBE is to be processed into Regenerated Spent Bleaching Earth (RSBE). This study aims to determine the adsorption capability of RSBE and the corresponding adsorption model on ion Fe(III). SBE processing into RSBE by extraction of oil on SBE soxhletation manner using n-hexane at a temperature of 72°C for 8 hours. Then the rest of the SBE results soxhletation washed with 3% HCl and physically activated at a temperature of 470oC. A total of 1 g RSBE mixed with a solution of Fe(NO3)3 with a volume of 100 ml at various concentrations (10, 15, 20, 25 and 30 ppm). The results showed that the adsorption RSBE reach equilibrium after a contact time of 150 minutes and adsorption that occurs following the Langmuir isotherm models with correlation coefficient (R2) = 0.982 and the maximum value jerap capacity = 2.71 mg Fe (III) / g RSBE.Keywords: adsorption, adsorption isotherms, ion Fe (III), RSBE, SBE